(untitled) - Schabas, William (Cambridge, U.K., 2001)
The author introducts to the International Criminal Court by providing a brief history of the evolution of its principles since the Nuremberg and Tokyo trials at the close of World War II through to its becoming operational and dealing with war crimes in Uganda and the Congo. It offers chapters discussing the Court's jurisdiction, the means by which jurisdiction is triggered, admissibility of cases, general principles of criminal law, investigation and pre-trial procedure, trial and appeal, punishment, victim participation and concerns, and the structure and administration of the Court.
Keywords: International criminal courts,Toà án hình sự Quốc tế